Dimensions of ciliary body structures in various axial lengths in patients with rhegmatogenous retinal detachment (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To investigate the dimensions of ciliary body structures in various axial eye lengths in patients with rhegmatogenous retinal detachment (RRD).Materials and Methods: This study included 35 RRD patients (35 eyes) with an intact fellow eye who were under observation. These were divided into three groups, based on axial length of the eye with RRD.  All patients underwent near-infrared transpalpebral transillumination (NIR TPT) and ultrasound scanning of the anterior eye.Results: In patients with axial length ranging from 20 mm to 22.9 mm, 23 mm to 24.9 mm, and larger than 25 mm, pars plana width was 3.4 mm, 4.16 mm, and 4.95 mm, respectively, whereas pars plicata width was 1.9 mm, 1.99 mm, and 2.0 mm, respectively, and pars plicata thickness was 0.75 mm, 0.75 mm, and 0.72 mm, respectively.Conclusions: A direct relationship exists between pars plana width and axial length, but pars plicata thickness and width do not depend on the axial length in eyes with RRD. There was no difference in pars plana width or pars plicata width between the eye with RRD and unaffected fellow eye. In the eye with RRD, the pars plicata thickness was thicker than that in the intact fellow eye, which may evidence the presence of intraocular inflammation.
Keywords: rhegmatogenous retinal detachment; infrared radiation; near-infrared transpalpebraltransillumination